Overcoming Barriers for Indonesia’s Women-Led Food SMEs in Export - Wibowo, Wahyudi; Kristyanto, Visi Saujaningati; Sutedjo, Purnomohadi (Research Synergy Foundation, 2025)
This study examines the export potential of women-led Small and Medium Enterprises (SMEs) in Indonesia's processed food sector by identifying key challenges and proposing targeted strategies for growth. Using a mixed-methods approach, the research surveyed 191 SMEs and collected qualitative insights through Focus Group Discussions and in-depth interviews with women entrepreneurs. An analytical framework was employed to classify their export readiness. The findings confirm that while these SMEs possess significant export potential, they are constrained by interconnected barriers, including limited access to finance, insufficient knowledge of international markets, low digital literacy, and socio-cultural obstacles. A key contribution of the study is the classification of SMEs into three tiers of export readiness: